2012
DOI: 10.1108/09684881211219352
|View full text |Cite
|
Sign up to set email alerts
|

What do teachers think about quality in the Spanish university?

Abstract: Purpose -This paper aims to present the opinions of teaching staff at Spanish universities regarding the relative importance of a number of quality factors, and perceived levels of development of those factors in the context of their work. Design/methodology/approach -The paper takes an empirical approach, with the opinions of teaching staff being collected via questionnaires and by telematic means. Findings -Lecturers surveyed are particularly pessimistic in regard to the conditions in which students enter un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Table IV indicates that teaching and communication (Q34), and evaluation of examinations (Q43) are consistently among the most important quality expectations by all key stakeholders. The results confirm the core value of higher education (Barandiaran et al , 2012; Hill et al , 2003; Mustafa and Chiang, 2006), and support efforts to encourage teaching excellence with innovative teaching and pedagogical research (Gibbs and Habeshaw, 2002). In addition, it was also observed that the validity of degree (Q45) is particularly critical to students, teaching staff and managerial staff, consistent with the findings of Srikatanyoo and Gnoth (2005).…”
Section: Analysis and Discussionsupporting
confidence: 69%
“…Table IV indicates that teaching and communication (Q34), and evaluation of examinations (Q43) are consistently among the most important quality expectations by all key stakeholders. The results confirm the core value of higher education (Barandiaran et al , 2012; Hill et al , 2003; Mustafa and Chiang, 2006), and support efforts to encourage teaching excellence with innovative teaching and pedagogical research (Gibbs and Habeshaw, 2002). In addition, it was also observed that the validity of degree (Q45) is particularly critical to students, teaching staff and managerial staff, consistent with the findings of Srikatanyoo and Gnoth (2005).…”
Section: Analysis and Discussionsupporting
confidence: 69%
“…It was noted that similar surveys involving university teaching staff tended to record fairly low response rates (Cardoso, Rosa, & Santos, 2013;Elmuti, Kathawala, & Manippallil, 1996;Kleijnen, Dolmans, Willems, & van Hout, 2011;Mather et al, 2007;Mather, Worrall, & Seifert, 2009;Watty, 2005Watty, , 2006. Surveys administered to similar populations (Barandiaran, Barrenetxea, Cardona, Mijangos, & Olaskoaga, 2012a, 2012b recorded response rates of around 33%; so the decision was made to send the questionnaire to approximately 3,000 lecturers, and therefore obtain a sample size of around 1,056 individuals, which is the lowest threshold for a representative sample size for the estimation of proportions, bearing in mind the size of the population, around 99,000 individuals (Spanish Ministry of Education, 2011), with a confidence level of 95% and a sampling error of 3%.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding students, academics confirmed the low involvement of students who should be considered as actors directly involved in the implementation of change (Nguyen, 2016) and as the second main stakeholder at the heart of the teaching and learning process (Barandiaran-Galdós et al, 2012;Elassy, 2015;Nguyen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they have been recognized for decades as essential actors with legitimate authority to express their views (Middlehurst, 1992). However, some research has revealed that academics are not frequently consulted and involved in the process of quality implementation and self-assessment (Cardoso & al, 2013), and they are not much solicited to give their views regarding it (Barandiaran-Galdós et al, 2012).…”
Section: Academic Perceptions Of Qualitymentioning
confidence: 99%